2008
DOI: 10.1186/1465-9921-9-39
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila infection induces programmed cell death, caspase activation, and release of high-mobility group box 1 protein in A549 alveolar epithelial cells: inhibition by methyl prednisolone

Abstract: Background: Legionella pneumophila pneumonia often exacerbates acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Apoptosis of alveolar epithelial cells is considered to play an important role in the pathogenesis of ALI and ARDS. In this study, we investigated the precise mechanism by which A549 alveolar epithelial cells induced by L. pneumophila undergo apoptosis. We also studied the effect of methyl prednisolone on apoptosis in these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…It was reported that TGF-␤ 1 -induced A549 cells to undergo EMT (12). Legionella pneumophila, which has flagella, was reportedly able to replicate within A549 cells (6).…”
mentioning
confidence: 99%
“…It was reported that TGF-␤ 1 -induced A549 cells to undergo EMT (12). Legionella pneumophila, which has flagella, was reportedly able to replicate within A549 cells (6).…”
mentioning
confidence: 99%
“…ARDS is characterized by flooded alveolar air spaces and increased microvascular and epithelial permeability due to neutrophil inflammation, damage to the alveolar capillary endothelium, and disruption of the alveolar epithelium. Apoptotic epithelial cells are found in the damaged alveolar epithelium of patients with ARDS, implicating such a mechanism in the pathogenesis of ALI and ARDS, including immune recovery and tissue repair after injury [27]. Apoptosis was also induced in L. pneumophila-infected alveolar epithelial cells, so L. pneumophila is considered to play a key role in cytotoxicity, and some alveolar epithelial cell injury induced by L. pneumophila was attributable to apoptosis of alveolar epithelial cells [27].…”
Section: Discussionmentioning
confidence: 98%
“…Both, in macrophages and alveolar epithelial cells the virulent strain of L. pneumophila induces programmed cell death, DNA fragmentation and activation of various caspases (32,33).…”
Section: Discussionmentioning
confidence: 99%